A HUMANISTIC MODEL FOR PUBLIC ORDER MANAGEMENT IN DENPASAR CITY - Subawa, Ida Bagus Gede; Wijaya, I Made Hendra; Lestari, AA Adi; Jaya Dhifa, Ngurah Galang (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Indonesia’s COVlD-19 first cinfirmed case was found in March 2020 and continued to increase until September 2020. As the number of cases increased, the government applied a Large-Scale Social Restrictions Policy (PSBB) to help minimize additional cases. With the implementation of the UN policy by the government, many have lost income from various sectors whose livelihoods depend on their daily income. The disruption of economic activity due to the lockdown policy to contain the spread of the virus has led to the closure and bankruptcy among many companies, resulting in a massive reduction in the number of workers and layoffs, especially in the sectors most affected by the pandemic. Many workers who are laid off make people lose their source of livelihood, forcing them to be more creative in order to struggle. One of them is the improvised street merchants, where the car is used as a selling space, which helps people in terms of economic turnover. However, selling on the roadside without a permit is an offence. The municipal police (Satpol PP) need to discipline the street merchants since they violate the Regional Regulation No. 1/2015 concerning Public Order. This regulation has been violated by many merchants and thus, it needs to be brought back into order. Keywords:  Fostering, street merchants